(untitled) (Damascus University Journal for engineering sciences, 2022)
In this research, a wide-band Vivaldi antenna was designed to pass the frequency band [2.33-7.09] GHz with a maximum gain of 6.62dB. This antenna was improved using Hybrid Kock-Minkowski fractal technique to become bandpass [2.209-7.09] GHz with a maximum gain of 8.26 dB and decrease side lobe levels. Thus, focus the radiation in the main lobe direction. The design of a human head model of four layers, namely skin, fat, skull and brain, whose dielectric properties were compatible with their natural values was designed by CST microwave Studio Suite package to test the efficiency of the antenna in and possibility of its implementation in the microwave imaging systems which Specific Absorption Rate (SAR) value in the case of a healthy brain meets international standards to ensure patients safety. The effectiveness of the proposed system in detecting brain injuries was confirmed through the formation of micro-images resulting from collecting signals reflected from the head to the proposed antenna. The using a confocal microwave imaging algorithm CMI based on the DAS delay and sum algorithm, injury site determination and image quality. MATLAB software is used to write the DAS based CMI algorithm.